Analisis Penerapan Asas Negativa Non Sunt Probanda pada Putusan Nafkah Lampau Nomor 262/Pdt.G/2017/PTA.Sby - Muhammad Kadafi Bashori (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
Abstract: The case of madliyah alimony between a former husband and wife was decided at the Mojokerto Religious Court through Decision No. 2343/Pdt.G/2015/PA.Mr dated February 22, 2017, which rejected the lawsuit because the wife (the counterclaimant) did not submit evidence. In the appeal, through Decision No. 262/Pdt.G/2017/PTA.Sby of the Surabaya High Religious Court dated June 2, 2017, the wife's lawsuit was granted because the appeal panel applied the principle of negativa non sunt probanda (negative matters do not need to be proven by the plaintiff). The emergence of Supreme Court Regulation (PERMA) No. 3 of 2017 was a response to bias and discrimination in the courts. The principle of gender equality in PERMA serves as a legal basis for judges to take a more substantively fair approach. This PERMA serves to correct unequal judicial practices and provides guidelines so that judges do not simply decide cases mechanically. The findings of this study are that the principle of negativa non sunt probanda is appropriate for application in lawsuits for past alimony because: It better aligns with the reality of the inequality of information and evidence in domestic relations. It protects women's rights from a disproportionate burden of proof. Procedural law reform is needed so that principles like this are not only used in a case-by-case manner, but become common practice in religious courts. It is important to encourage justice based on substantive justice,not just formal justice.Keywords: Principle Negativa Non Sunt Probanda, Proof, Past Livelihood, Court Ruling Abstrak: Perkara nafkah madliyah antara mantan suami dan istri diputus di Pengadilan Agama Mojokerto melalui Putusan No. 2343/Pdt.G/2015/PA.Mr tertanggal 22 Februari 2017, yang menolak gugatan karena istri (penggugat rekonvensi) tidak mengajukan alat bukti. Dalam banding, melalui Putusan Pengadilan Tinggi Agama Surabaya No. 262/Pdt.G/2017/PTA.Sby tanggal 2 Juni 2017, gugatan istri dikabulkan karena majelis banding menerapkan asas negativa non sunt probanda (hal negatif tidak perlu dibuktikan oleh penggugat). Munculnya Peraturan Mahkamah Agung (PERMA) No. 3 Tahun 2017 sebagai respons terhadap bias dan diskriminasi di pengadilan. Asas kesetaraan gender dalam PERMA menjadi dasar hukum bagi hakim untuk mengambil pendekatan yang lebih adil secara substantif. PERMA ini berfungsi untuk mengoreksi praktik peradilan yang timpang dan memberi pedoman agar hakim tidak sekadar memutus perkara secara mekanistik. Adapun temuan dari penelitian ini Adalah Asas negativa non sunt probanda layak diterapkan dalam gugatan nafkah lampau, karena: Lebih sesuai dengan realitas ketimpangan informasi dan bukti dalam relasi rumah tangga. Melindungi hak-hak perempuan dari beban pembuktian yang tidak proporsional. Dibutuhkan pembaruan hukum acara agar asas-asas seperti ini tidak hanya digunakan secara kasuistik, tetapi menjadi praktik umum dalam peradilan agama. Penting untuk mendorong peradilan yang berkeadilan substantif, bukan hanya formal.Kata Kunci: Asas Negativa Non Sunt Probanda, Pembuktian, Nafkah Lampau, PutusanPengadilan